Sistem Informasi Geografis Dan Proyeksi Penduduk Kabupaten Pohuwato Tahun 2035 Dengan Metode Aritmatik - BULAN SUCI RAMADHANI; Titi Hawanda Metania Cono (Geosfera: Jurnal Penelitian Geografi, 2025)
This study examines the projected population in Pohuwato Regency in the future in 2035 using the Arithmetic method. Given that the presentation of projection data is generally only in the form of tables and graphs, the purpose of this study is to present complete projection data both in the form of tables, graphs and visually in the form of maps. The research method used is quantitative analysis. The results of the study show that the projected population of Pohuwato Regency in 2034 is estimated arithmetically to be 191,499 (people). Based on the map visualization, there are 3 classes, namely low, medium and high. The low classification is Wanggarasi, Dengilo, Taluditi, West Popapato, East Popayato, and Popayato. The classification of the projected medium population is Buntulia, Duhiadaa, Lemito, Paguat, and Patilanggio Districts. As for the projection of high population, is Marisa and Randangan Districts.